Management and promotion of martial arts, across disciplines and styles - Wojciech J. Cynarski (International Martial Arts and Culture Journal, 2025)
Perspective: Among the many martial arts, disciplines, and styles, only a few have achieved global renown. Managing a company or other martial arts organization requires promotional activities. The broader concept of marketing and the General Theory of Fighting Arts provide the theoretical foundation for this discussion. Problem: Are there any relationships between the type of promotional activities and fame, popularity, and measurable organizational success? How does presence in popular culture (films, books, celebrities) contribute to the international popularity of a given martial art style?. Method: A multiple case study was conducted for five relatively popular martial arts styles. Promotion of the style in films, books, through celebrities, international organizations, and the history of the master was considered. Included: 1) Kyokushin karate; 2) Wing Tsun kung fu; 3) American kenpo karate; 4) Jeet Kune Do kung fu; 5) Chuck Norris System. Results: International popularity is achieved only through a combination of the following promotional activities: film appearances, books, celebrity students, and organizational development. Conclusions: In the absence of such activities, the distinguished master-teacher and his school remain largely unknown or little known. Particularly in martial arts that reject competitive sports, it is difficult to achieve greater international popularity.